Perancangan Sistem Informasi Bimbingan Skripsi Berbasis Mobile - Thomson Mary; Ade Pratama; Annisa Syafira (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This thesis guidance information system was made for the Informatics Education Study Program of STKIP PGRI West Sumatra. The problem raised from this thesis guidance application program is that the guidance is carried out face-to-face and due to Covid19 makes the thesis guidance process constrained due to the implementation of Physical and Social distancing. In addition, the matching of time between students and lecturers hampered the guidance process. So for that a computerized and programmed system was created by making a Mobile-based thesis guidance application. This thesis guidance information system is designed using the Unified Modeling Language (UML) model and uses the Software Development Life Cycle (SDLC) method, which in this method has several stages, namely the planning stage, the analysis stage, the design stage, the implementation stage, the testing stage and the maintenance By using the SDLC method and the UML model, it is expected to be able to produce a Mobile-Based Thesis Guidance Application to overcome problems and to facilitate the guidance process that will be carried out by students and supervisors.